Development and Characterization of a Biodegradable Colored Film Based on Starch and Chitosan by Using Acacia Catechu - Quader, FB; Khan, RA; Islam, MA; Saha, S; Sharmin, KN (Journal of Environmental Science and Natural Resources, 2016)
Green technology like biodegradable films using natural polymer is an obvious need of today. Attempt of this experiment was aimed at development and characterization of a biodegradable colored film based on starch and chitosan by using Acacia catechu. Chitosan reinforced starch based biodegradable composite film was prepared by casting. The chitosan content in the films was varied from 20-80 % (w/w). Tensile strength (TS) was improved significantly with the addition of chitosan but the elongation at break (EB %) of the composite decreased. With the addition of the Acacia catechu, tensile strength of the composites improved more. The acacia content of the film was varied from 0.05-0.2(w/w). The good thermal stability of this prepared film was confirmed by thermo-gravimetric analysis. Structural characterization was done by Fourier transform infrared radiation spectroscopy. Surface morphology of the composite film was examined by scanning electron microscope (SEM) which suggested sufficient homogenization of starch, chitosan and Acacia catechu. Water uptake was found lower for final composites in the comparison to starch/chitosan and chitosan film. The satisfactory rate of degradation in the soil is expected that the final composite film within less than 6 months. The developed films intended to use as the alternative of synthetic non biodegradable colored packaging films. J. Environ. Sci. & Natural Resources, 8(2): 123-130 2015